Say we have an equation $ax^2 + bx - c = 0$ and want to find $x$. Obviously the way to solve would be to use the quadratic equation or factorize. I understand that saying $$ax^2 + bx = c => x(ax + b) = c$$ and then solving is wrong (the values of $x$ when subbed back in do not satisfy the eqn), but why is it wrong? Each step seems logical?

Many thanks.

  • $\begingroup$ All too often in your past experience, you have been given quadratic equations $ax^2+bx-c=0$ which have integer solutions. Then rewriting as $x(ax+b)=c$ and testing for $x$ various divisors of $c$ is a strategy that works. Of course, some divisors may not work, but that's no problem, you have found a solution. However, if the quadratic has no integer solutions (and most of them don't) then the procedure breaks down. $\endgroup$ – André Nicolas Dec 23 '12 at 21:34

The equation $x(ax+b) = c$ is valid but does not help. There is a general fact that $AB = 0$ implies $A = 0$ or $B=0$ and this allows us to solve a product expression by reducing it to easier equations. So we need 0 on the right hand side of the product to be useful.

e.g. we want to rewrite your equation $ax^2 + bx - c = 0$ as $a(x+\alpha)(x+\beta) = 0$.

In order to find $\alpha, \beta$ to do this, note that we ensured the quadritic term is already OK: $ax^2$ in both. The linear term is $a(\alpha+\beta) = b$ and the constant term is $a\alpha\beta = -c$. So you need to find $\alpha$ and $\beta$ with known sum $\frac{b}{a}$ and known product $\frac{-c}{a}$, and this can sometimes be seen by inspection for concrete $a,b$ and $c$.


The factorization is wrong. We need to reach at $(ax-\alpha)(x-\beta)=0$ so that we can say either $ax-\alpha=0$ or $x-\beta=0$

  • $\begingroup$ That is clear, but is there a reason why the method I showed does not work? $\endgroup$ – CAF Dec 23 '12 at 15:24
  • $\begingroup$ If the product of two terms involving $x$ is some given constant, how can we get the value of $x?$ $\endgroup$ – lab bhattacharjee Dec 23 '12 at 15:25
  • $\begingroup$ Multiplying out those terms and rearranging such that we have $0$ on the RHS. I realise this is the way to solve, but why does the method I give not work? Consider the simple case $x^2 + 4x + 3 = 0$. By factoring as a product of two binomials gives $x = -3, -1$. Now say $x^2 + 4x = -3 $ and write $x(x+4) = -3$ and then $x = -3, -7$ Where is the error in this method? $\endgroup$ – CAF Dec 23 '12 at 15:38
  • $\begingroup$ @CAF, we need to replace $x$ in both places in the left hand side with the value like $-3$ etc. $-3,-1$ would make $-3=-3$ which is true, but $-7$ would make $(-7)(-1)=-3$ which is false.Hence $-3,-1$ are solutions unlike any other value. $\endgroup$ – lab bhattacharjee Dec 23 '12 at 15:42
  • $\begingroup$ I understand this is wrong, but is there an underlying reason? As I said, each step seems logical and there seems to be no a priori assumptions about $x$ at each stage. $\endgroup$ – CAF Dec 23 '12 at 15:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.